Person to person customer service [videorecording] (Customer service essentials, 2012)
This video shows employees how to achieve that goal, using lively animation, no-nonsense explanations, and clear, entertaining dramatizations. Topics include creating a good first impression, developing a professional and outgoing attitude, following customer service procedures in a logical manner, and handling conflict calmly, confidentially, and respectfully.